Prevalensi Ektoparasit pada Benih Ikan Koi Cyprinus rubrofuscus (Lacepede, 1803) di Sentra Budidaya Kabupaten Blitar - Salsabila Mumtasah; Lud Waluyo; Husamah Husamah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The problem of koi fish farming in Blitar Regency that is causing concern and has not been resolved is a disease caused by ectoparasites. The purpose of this study was to observe the types of ectoparasites and the prevalence of parasites that attack koi fish in cultivation centers in Blitar Regency. This type of research is descriptive research with a survey method approach. The koi fish sampled were koi fish fingerlings measuring 7-15 cm in the Kohaku, Tancho, Ogon, and Utsuri varieties with three individuals each. Sampling using purposive sampling technique. Examination of ectoparasites was carried out by cutting the body parts of the fish (fins, gill lamellae, and tail), then placing them on a glass slide, dripping with distilled water, covering with a cover glass, and observing under a microscope. The results of the ectoparasites examination were analyzed descriptively quantitatively. The data obtained is tabulated in tables and graphs and paired with related literacy. The results showed that there were 5 types of ectoparasites, namely: Lerneaea sp., Argulus sp., Trichodina sp., Dactylogyrus sp., and Gyrodactylus sp., with different numbers and prevalence in each variety. The highest prevalence of ectoparasites in 4 varieties of koi fish was in the Ogon variety (66.6%) with the very frequent infection category, and the lowest in the Kohaku, Tancho, and Utsuri varieties (33%) with the general infection category. The highest prevalence of each type of ectoparasites was Gyrodactylus sp., amounting to 66.6% (very frequent infections) with 3 individual parasites, and Dactylogyrus sp., amounting to 33% -66.6% (general infections - very frequent) with 7 individuals.